Emergence of verb-pattern morphology in young Arabic speakers: morphological and semantic features - Tallas-Mahajna, Naila; Armon-Lotem, Sharon; Saiegh-Haddad, Elinor (Frontiers in Psychology, 2023)
Arabic, a Semitic language, displays a particularly rich derivational morphological system with all verb stems consisting of a semantic root and a prosodic verb-pattern. Such regular and frequently encountered knowledge is expected to be acquired early. The present study presents a developmental perspective on the relative contribution of morphological and semantic complexity to the acquisition of verbs in Spoken Arabic. Verbs in a spontaneous corpus from 133 typically developing children, 2;6–6;0-year-old, were coded for type and token frequency of verbal patterns and root type, and classified according to semantic complexity. Results support an item-based emergence driven by semantic complexity at the earliest stages of acquisition. A developmental expansion in the diversity of verbal patterns and morphological complexity was observed with age. Morphological complexity is only identified when the same root appears in different verb patterns. It is concluded that increase in morphological complexity is bound by semantic complexity.